Design of Planetary Gear for Vertical Axis Marine Current Turbine - Achmad Baidowi; Irfan S.Arief; Aan A. Hendrianto; Fadil hafuza (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Indonesia as the archipelagic country in the world offers an abundant resource of ocean energy and one of them is marine current energy. One of the key concept of designing marine current energy converter is the gearbox. This paper discusses the design of gearbox using planetary gear to transmit power from 27RPM current turbine to a 5kW generator with 200RPM and 269Nm input torque. This paper presented the comparison of single stage planetary gear and double stage planetary gear from the aspect of maximum stress and the weight design. From the aspect the maximum stress, both of the gear design still under the limitation of the material stress, while based on the weight perspective the single stage has lower weight compared to double stage of planetary gear but from the size perspective the single stage has a larger diameter compared to the double stage planetary gear.